Molecular Identification and Analysis on Differential Pathogenicity of Cylindrocarpon Species Associated With Ginseng Root Rust Rot in Northeastern China - Li, Zibo; Sun, Chunlei; Liu, Xinran; Zhou, Rujun (Frontiers in Plant Science, 2022)
Panax ginseng C. A. Meyer is one of the most important medicinal herbs in China. It is known for its high medicinal value and economic value. The ginseng root rust rot (RRR) has always been one of the important diseases troubling the ginseng industry. The yield reduction rate of RRR is about 30%. In order to understand why the Cylindrocarpon species bring about the ginseng RRR in Northeastern China, this study isolated 45 strains from samples collected in Liaoning, Jilin and Heilongjiang provinces. The rDNA-ITS sequence was analyzed to identify the pathogenic species. The morphological characteristics of colonies and conidia of each strain on PDA medium were observed, and the pathogenicity difference between different pathogenic species was analyzed by pricking method and determining the cell wall degrading enzyme activity. The BLAST alignment analysis shows that the homology of rDNA-ITS between 45 strains and Cylindrocarpon is more than 99%, among which 28 are identified as Cylindrocarpon destructans, three are Cylindrocarpon destructans var. destructans and 14 are Ilyonectria robusta. The colony diameters of all 45 isolated range from 4.21±0.16a to 7.78±0.25c cm after several days of incubation. Among all the species, the Ilyonectria robusta has the fastest growth rate and Cylindrocarpon destructans var. destructans has the slowest growth rate. Pathogenicity tests results shows that the pathogenicity of Cylindrocarpon destructans var. destructans is the strongest, followed by Cylindrocarpon destructans. Ilyonectria robusta has relatively weak pathogenicity.